P2X receptor antagonists for pain management: examination of binding and physicochemical properties - Gum, Rebecca J. (Springer Netherlands, 2011)
Enhanced sensitivity to noxious stimuli and the perception of non-noxious stimuli as painful are hallmark sensory perturbations associated with chronic pain. It is now appreciated that ATP, through its actions as an excitatory neurotransmitter, plays a prominent role in the initiation and maintenance of chronic pain states. Mechanistically, the ability of ATP to drive nociceptive sensitivity is mediated through direct interactions at neuronal P2X3 and P2X2/3 receptors. Extracellular ATP also activates P2X4, P2X7, and several P2Y receptors on glial cells within the spinal cord, which leads to a heightened state of neural-glial cell interaction in ongoing pain states. Following the molecular identification of the P2 receptor superfamilies, selective small molecule antagonists for several P2 receptor subtypes were identified, which have been useful for investigating the role of specific P2X receptors in preclinical chronic pain models. More recently, several P2X receptor antagonists have advanced into clinical trials for inflammation and pain. The development of orally bioavailable blockers for ion channels, including the P2X receptors, has been traditionally difficult due to the necessity of combining requirements for target potency and selectivity with suitable absorption distribution, metabolism, and elimination properties. Recent studies on the physicochemical properties of marketed orally bioavailable drugs, have identified several parameters that appear critical for increasing the probability of achieving suitable bioavailability, central nervous system exposure, and acceptable safety necessary for clinical efficacy. This review provides an overview of the antinociceptive pharmacology of P2X receptor antagonists and the chemical diversity and drug-like properties for emerging antagonists of P2X3, P2X2/3, P2X4, and P2X7 receptors.